Pengaruh Metode Pembelajaran Gallery Walk Terhadap Hasil Belajar Mata Pelajaran Fiqih Siswa Kelas VIII MTs Muhammadiyah 11 Dengok Paciran Lamongan Tahun Pelajaran 2023/2024 - Mazro'atul Jannah dan Maftuhah (Jurnal Mahasiswa Pendidikan, 2024)
Abstract: The reality in the world of education, especially in fiqh subjects, teachers tend to still use conventional methods that make students get bored quickly. The Gallery Walk method is one of the fun learning methods and requires cooperation between students so that students can be more active and not quickly feel bored during learning. The Gallery Walk method can also be one of the solutions to the problems discussed in the study, namely students who feel bored and tend to be unfocused and less active as well as subject matter that is not understood by students The purpose of this study is to find out the influence of the Gallery Walk method on student learning outcomes. This study uses a quantitative method with parametric data analysis techniques, as well as a pre-experimental design (one-group pretest-posttest design), the subject of the research is a student of Class VIII Mts Muhammadiyah 11 Dengok Paciran Lamongan. The data collection technique in this study uses observation, tests, and documentation. The results of this study used a product moment correlation test, as well as a significance test (t-test). From the results of the data analysis carried out, this data was declared to be valid, reliable, normal, homogeneous. There was a significant correlation between variable X and variable Y. A correlation value of 0.444 was obtained with a table value = 0.3882, and a significance test result of 2.422 was obtained with a table value = 2.604. Therefore, it can be concluded that there is an influence between the Gallery Walk method and the learning outcomes of grade VIII students of Mts Muhammadiyah 11 Dengok Paciran Lamongan